Physics Achievement Test Implies Students’ Self-Efficacy on Decision Making Process - Dian Mayasari; Riski Muliyani; Yudi Kurniawan; Iip Istirahayu (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
This research was conducted to provide a comprehensive description about how the results of the cognitive learning outcomes of the physics field were indirectly supported by self-efficacy in the decision making process of the beliefs of the chosen answers. This research is descriptive qualitative research and involves 24 samples of class X students. The sample technique chosen was purposive sampling. The testing of cognitive learning outcomes in cognitive domains was conducted and designed by physics education lecturers and self-efficacy testing carried out and designed by lecturers in the direction of guidance and counseling using attitude scales. This combination of measurements produces two decisions on self-efficacy: positive and negative. The results of the study showed that students with high self-efficacy got high scores also on the physics test of cognitive learning outcomes. These students are classified as students with positive self-efficacy. Conversely, negative self-efficacy shows that students have high self-efficacy but get low cognitive test results in cognitive domains. These results are certainly influenced by several factors including uncertainty and anxiety.